TANTANGAN PERGESERAN KELEMBAGAAN PKK DI PEDESAAN PERSPEKTIF ISOMORFISME - Emi Hidayati (Department of Islamic Community Development, Faculty of Dakwah,Universitas Islam Ibrahimy Banyuwangi, 2024)
This study aims to understand the institutional dynamics of the Family Welfare Development (PKK) in Indonesia through the framework of institutional isomorphism theory. The rationale behind this research is the significant impact of changing government regulations and policies on the structure and operations of PKK since its inception. Based on the institutional isomorphism theory by DiMaggio and Powell (1983), this research explores how PKK experiences coercive, mimetic, and normative isomorphism in response to external pressures. Other theories used include the power and control structures by Pfeffer and Salancik (1978), organizational adaptation by Aldrich and Pfeffer (1976), legitimacy by Suchman (1995), and organizational innovation by Tushman and O'Reilly (1996). This study employs a descriptive qualitative method . Data were collected through in-depth interviews, document analysis, and participatory observation, with triangulation to ensure the validity and reliability of the findings. The results indicate that PKK experiences coercive isomorphism through adjustments to government regulations such as Presidential Decree No. 28 of 1980 and Minister of Home Affairs Regulation No. 18 of 2018, mimetic isomorphism by adopting successful practices from other organizations, and normative isomorphism through professionalization and standardization within PKK. The key findings reveal that PKK tends to be less independent, heavily reliant on government funding sources, and its structure is integrated into the government bureaucracy. This pattern of institutional change highlights the importance of understanding and managing these dynamics to achieve better family empowerment.